Genesis of Arabic Oratory - Feruza Shukurovna Djuraeva (Researchparks Publishing, 2023)
This article is dedicated to the study of the most important and always relevant topic of literary studies, the history of the art of speech, in particular, the beginning of the Arabic art of speech, the history of the world-famous Arabic oratory. The author tries to find out that the history of Arabic literature, whether it is prose or verse, which existed before Islam, is related to the innate skill in the art of words of the Arab people, and the factors that served the birth and development of this eloquence.